The reception of young mothers in Surabaya toward Nikita Williy’s Mom’s Corner YouTube content - Shafira Arinayah Putri; Hajidah Fildzahun Nadhilah Kusnadi; Edy Sudaryanto (C-DISC, 2026)
This study examines young mothers’ reception of Nikita Willy’s YouTube content, Mom’s Corner, on newborn care and breastfeeding. In the digital era, knowledge about childcare has increasingly shifted from family traditions to social media-based sources. This study employed a descriptive qualitative approach using Stuart Hall’s reception analysis, supported by the concepts of family communication and early childhood development during the golden age (0–5 years). Data were collected through documentation of two selected videos, focus group discussions, and individual interviews with ten informants. The findings reveal that audience reception is diverse rather than uniform. A dominant reading emerged when participants perceived the content as medically credible and relevant to their needs. The negotiating position was most prevalent, with informants accepting the educational value of the content while adapting it to their children’s and families’ circumstances. An oppositional reading appeared only in limited cases, as some participants prioritized personal experience over digital references. These findings demonstrate that young mothers are active audiences who interpret digital childcare content by integrating medical knowledge, personal experience, family communication, and the developmental needs of young children.